32.5k views
0 votes
Prove that an = 4^n + 2(-1)^nis the solution to

therecurrence relation an = 3an-1
+4an-2 for n>=2.

User Jiriki
by
5.3k points

1 Answer

5 votes

Answer:

See proof below

Explanation:

We have to verify that if we substitute
a_n=4^n+2(-1)^n in the equation
a_n=3a_(n-1)+4a_(n-2) the equality is true.

Let's substitute first in the right hand side:


3a_(n-1)+4a_(n-2)=3(4^(n-1)+2(-1)^(n-1))+4(4^(n-2)+2(-1)^(n-2))

Now we use the distributive laws. Also, note that
(-1)^(n-1)=(1)/(-1)(-1)^n=(-1)(-1)^(n) (this also works when the power is n-2).


=3(4^(n-1))+6(-1)^(n-1)+4(4^(n-2))+8(-1)^(n-2)


=3(4^(n-1))+(-1)(6)(-1)^(n)+4^(n-1)+(-1)^2(8)(-1)^(n)


=4(4^(n-1))-6(-1)^(n)+8(-1)^(n)=4^n+2(-1)^n=a_n

then the sequence solves the recurrence relation.

User Andrew McGivery
by
5.8k points